Studi Pelepasan Beban Dengan Menggunakan Relai Frekuensi Kurang Pada Sistem Tenaga Listrik - Abdul Hadi; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This paper discusses about load shedding scheme using under frequency relay in Teluk Lembu substation PT. PLN electric power system. Load shedding is used as an effort to improve the unstable system frequency because of overload condition. Load shedding is expected to improve the frequency rapidly and the amount of load shed as minimum as possible. To prove the effectiveness of load shedding scheme used by PLN, do a comparison with the load shedding scheme using trial and error method. Simulation of load shedding is using ETAP software version 12.6.0. From the simulation, load shedding scheme owned PLN is still effective against the condition of decreasing frequency.Keywords: Load shedding, frequency, under frequency relay, ETAP